Minimally invasive medial femoral approach to total knee arthroplasty improves short-term outcomes compared to the standard medial parapatellar approach: a systematic review and meta-analysis - Xin Yang; Qing-hao Cheng; Yong-ze Yang; An-ren Zhang; Hua Fan; Hong-zhang Guo (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Objective The aim of this study is to conduct a comprehensive evaluation of the effectiveness of the medial parapatellar approach via the vastus medialis obliquus muscle in comparison with the standard medial parapatellar approach for total knee arthroplasty, using a systematic approach. Methods A computer search was conducted on PubMed, EMBASE, Medline, Cochrane libraries, and Web of Science databases to comprehensively collect randomized controlled studies on minimally invasive (MMV) approaches for knee arthroplasty, specifically the vastus and medial parapatellar (MP) approaches. Two authors independently screened the literature based on inclusion and exclusion criteria, evaluated the quality of the included studies using the Cochrane systematic review method, and performed a meta-analysis using RevMan 5.3 software. Results A total of twelve randomized controlled studies were ultimately included, comprising 788 knees. The small incision medial femoral muscle approach (MMV) group consisted of 398 cases, while the traditional parapatellar approach (MP) group consisted of 390 cases. Data analysis showed that in the comparison of KSS, VAS, and ROM score at 3 months after surgery, MMV approach was superior to MP approach [MD = 2.89, 95%CI (0.33, 5.46), P = 0.03], [MD = − 0.22, 95%CI (− 0.36, − 0.09), P = 0.001], and [MD = 1.08, 95%CI (0.04, 2.12), P = 0.04]. However, there was no significant difference in the postoperative KSS, VAS, and ROM score between the MMV and MP approaches at 6 and 12 months after surgery. The operation time of the MMV group was longer than that of the MP group [MD = 8.98, 95%CI (4.64, 13.32), P < 0.0001], and the number of days of straight leg raising after surgery was shorter in the MMV group than in the MP group [MD = − 1.91, 95%CI (− 3.45, − 0.37), P = 0.01], with statistically significant differences. There was no significant difference in the lateral support band release rate [OR = 0.72, 95%CI (0.23, 2.28), P = 0.58], length of hospital stay [MD = 0.07, 95%CI (− 0.18, 0.31), P = 0.58], postoperative complications [MD = 0.62, 95%CI (0.33, 1.18), P = 0.15], and intraoperative blood loss [MD = 70.50, 95%CI (− 57.51, 198.72), P = 0.28]. Conclusion Most of the approaches have similar length of stay and incidence of complications compared to standard approaches. However, the minimally invasive midvastus approach has shown potential to improve short-term outcomes. Study registration: PROSPERO registration number CRD42023410583.